2020
DOI: 10.1002/ajpa.24159
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of stone tool production among novice and expert tool makers

Abstract: Objectives: As is the case among many complex motor tasks that require prolonged practice before achieving expertise, aspects of the biomechanics of knapping vary according to the relative experience/skill level of the practitioner. In archaeological experiments focused on the production of Plio-Pleistocene stone tools, these skill-mediated biomechanical differences have bearings on experimental design, the interpretation of results, and lithic assemblage analysis. A robust body of work exists on variation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Third, more muscles articulate the human than the macaque thumb (Diogo and Wood, 2012). All of these differences contribute to increased manipulative ability of humans, exemplified by tool-making and strong precision grip (Young, 2003;Kivell et al, 2011;Rolian et al, 2011;Karakostis et al, 2021;Williams-Hatala et al, 2021). We found that the thumb was the most independent digit in both humans and monkeys and the thumb was a significant contributor to the dissimilarity between human and monkey prehensile kinematics.…”
Section: Kinematic Similarities and Differencesmentioning
confidence: 70%
“…Third, more muscles articulate the human than the macaque thumb (Diogo and Wood, 2012). All of these differences contribute to increased manipulative ability of humans, exemplified by tool-making and strong precision grip (Young, 2003;Kivell et al, 2011;Rolian et al, 2011;Karakostis et al, 2021;Williams-Hatala et al, 2021). We found that the thumb was the most independent digit in both humans and monkeys and the thumb was a significant contributor to the dissimilarity between human and monkey prehensile kinematics.…”
Section: Kinematic Similarities and Differencesmentioning
confidence: 70%
“…The biomechanics of the type of free-hand knapping used for making the core tools and flakes that typify the Oldowan has received more attention (e.g., Bril et al, 2010;Hamrick et al, 1998;Key & Dunmore, 2015;Marzke & Shackley, 1986;Marzke et al, 1998;Mateos et al, 2019;Williams et al, 2010), but research focused on the hand is comparatively limited, making it difficult to evaluate functional and adaptive hypotheses. What we do know regarding hand function during free-hand knapping is that a wide variety of grips are used, with a significant emphasis on precision grips (Key et al, 2018;Williams-Hatala et al, 2021). Loads tend to be concentrated on the pollex in both the dominant (Rolian et al, 2011;Williams-Hatala et al, 2018;Williams-Hatala et al, 2021, contra Williams et al, 2012 and non-dominant hands (Key & Dunmore, 2015), followed by the second ray, whereas the ulnar rays on both hands experience significantly lower loads (Key et al, 2019;Williams-Hatala et al, 2018.…”
Section: Hominin Hand Evolutionmentioning
confidence: 99%
“…What we do know regarding hand function during free‐hand knapping is that a wide variety of grips are used, with a significant emphasis on precision grips (Key et al, 2018; Williams‐Hatala et al, 2021). Loads tend to be concentrated on the pollex in both the dominant (Rolian et al, 2011; Williams‐Hatala et al, 2018; Williams‐Hatala et al, 2021, contra Williams et al, 2012) and non‐dominant hands (Key & Dunmore, 2015), followed by the second ray, whereas the ulnar rays on both hands experience significantly lower loads (Key et al, 2019; Williams‐Hatala et al, 2018, 2021). High loads on the first ray correlate with increased flexor pollicis longus (FPL) activity in other behaviors (Basmajian & De Luca, 1985; Hamrick et al, 1998), which was confirmed by two studies of muscle activity during free‐hand knapping (Hamrick et al, 1998; Marzke et al, 1998).…”
Section: Part 3: Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, manual pressure sensors like dynamometers (Key & Lycett, 2011;Key, 2013) or Novel Pliance® gloves also stand out to examine the distribution of pressure exerted with the hands during the reproduction of archaeological tasks (Putti et al, 2007;Williams et al, 2012;Price et al, 2016;Williams-Hatala et al, 2020) (Fig. 1c).…”
Section: Digital Innovation In Experimental Bioarchaeologymentioning
confidence: 99%